Analysis of patient‐specific NF1 variants leads to functional insights for Ras signaling that can impact personalized medicine. Issue 1 (15th November 2021) - Long, Ashlee; Liu, Hui; Liu, Jian; Daniel, Michael; Bedwell, David M.; Korf, Bruce; Kesterson, Robert A.; Wallis, Deeann
Abstract: We have created a panel of 29 NF1 variant complementary DNAs (cDNAs) representing missense variants, many with clinically relevant phenotypes, in‐frame deletions, splice variants, and nonsense variants. We have determined the functional consequences of the variants, assessing their ability to produce mature neurofibromin and restore Ras signaling activity in NF1 null (−/−) cells. cDNAs demonstrate variant‐specific differences in neurofibromin protein levels, suggesting that some variants lead to neurofibromatosis type 1 (NF1) gene or protein instability or enhanced degradation. When expressed at high levels, some variant proteins are still able to repress Ras activity, indicating that the NF1 phenotype may be due to low protein abundance. In contrast, other variant proteins are incapable of repressing Ras activity, indicating that some do not functionally engage Ras and stimulate GTPase activity. We observed that effects on protein abundance and Ras activity can be mutually exclusive. These assays allow us to categorize variants by functional effects, may help to classify variants of unknown significance, and may have future implications for more directed therapeutics. Abstract : NF1 variants differentially effect neurofibromin abundance and Ras signaling in vitro.